Bacon et la méthode : la libération de l’invention - Luc Peterschmitt (Revue LISA)
In this article, I examine how Bacon is able to justify his promise that the new way he proposes to follow in science is fruitful. I show that such a promise makes sense only if Bacon does not claim that he totally rejects past philosophy. If this were the case, then even the bare possibility of knowledge could not be warranted and Bacon would be a mere sceptic. This leads me to reassess Bacon’s claim to novelty and rupture with past philosophers. I take such a claim to be mainly a rhetorical strategy aiming at preventing men from being satisfied with their present knowledge. In its turn, such a strategy implies that progress must be infinite and that it is impossible to determine completely a priori the way that must be followed to produce new knowledge. One can give but indications, which may always be improved, according to the progress of knowledge. In this sense, it is not possible to foresee progress : nobody can tell what knowledge will be. That is why one may say that Bacon’s philosophy aims at setting invention free.